Natural preservatives in meat products - Sośnicka, Marta (Biotechnology and Food Science, 2019)
The use of preservatives in industrial food production is now common practice. However, there is growing concern among consumers over the harmful effectsof common chemical preservatives. As a result, there is inc reased demand for food that that has undergone little or no processing. In recent years, there has therefore been great interest in fi nding alternatives to chemical preservatives for use in the meat industry, in the form of natural ingredients. Possible solutions in clude the use of plant extracts, essential oils or antimicrobial pepti des. This paper provides a review of research on the replacement of artificial preservatives in meat products with traditional chemical compounds of natural origin.